3D Visualization and Virtual Exploration of Genomic Sequences - J Hérisson; N Férey; P E Gros; O Magneau; R Gherbi (Data Science Journal, 2006)
In this paper, we address the potential offered by Virtual Reality for 3D modeling and immersive visualization of large genomic sequences. The representation of the 3D structure of DNA allows biologists to observe and analyze genomes in an interactive way at different levels. We developed a powerful software platform that provides a new point of view for sequences analysis: ADN-Viewer. Nevertheless, a classical eukaryotic chromosome of 40 million base pairs requires about 6 Gbytes of 3D data. In order to manage these huge amounts of data in real-time, we designed various scene management algorithms and immersive human-computer interaction for user-friendly data exploration.